DAMPAK VARIABEL MAKROEKONOMI PADA VOLATILITAS PADA PASAR MODAL SYARIAH INDONESIA: Pendekatan Model Error Correction - wahyudi, setyo tri; Nabella, Rihana Sofie (Buletin Studi Ekonomi, 2020)
Indonesia's sharia capital market continues to develop and become an alternative investment. Compared to conventional capital markets, sharia capital markets are believed to be stronger against crises, changes in economic fundamentals and financial market shocks. This study aims to analyze the effect of macroeconomic variables on Indonesia Sharia Stock Index. This research uses Error Correction Model (ECM) method. The results of this study are the rising exchange rate and world crude oil price will decrease Sharia Index of Indonesia Shares (ISSI), in the long run and short term increase of BI Rate will increase Sharia Index of Indonesia (ISSI) and inflation rate does not affect Indonesia Sharia Index ( ISSI).